THE IMPACT OF STRESS AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES IN THE SIANTAR CITY MANPOWER DEPARTMENT - Binur Pretty Napitupulu; Haervi Yunira (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Work stress and motivation are two factors that can influence the increase or decrease in employee performance. This study aims to determine and analyze the effect of work stress and work motivation on employee performance at the Siantar City Manpower Office. The focus of the study is limited to two independent variables, namely work stress and work motivation, and one dependent variable, namely employee performance. The formulation of the problem raised is whether work stress and work motivation affect employee performance. The population in this study amounted to 58 people who were also used as samples. The approach used is quantitative, with data collection through questionnaires and using secondary data. The data analysis technique used is multiple linear regression, with hypothesis testing through the t-test (partial), F-test (simultaneous), and the Coefficient of Determination (R²). The results of the study show a regression model Y = 0.550 + 0.447X₁ + 0.398X₂, where X₁ is work stress and X₂ is work motivation. Partially, work stress has a significant effect on employee performance with a significance value of 0.001 (<0.05) and a t-count of 3.543 (> t-table 1.673). Work motivation also shows a partial significant effect with a significance value of 0.002 (<0.05) and a t-count of 3.225 (> t-table 1.673). Simultaneously, both variables have a significant effect on employee performance, with a significance value of 0.000 (<0.05) and an F-count of 34.156 (> F-table 3.17). The coefficient of determination (R²) of 0.554 indicates that 55.4% of the variation in employee performance is influenced by work stress and work motivation, while the remaining 44.6% is influenced by other factors outside this study. Thus, the relationship between work stress, work motivation, and employee performance is quite strong but not dominant.